Challenging Corruption: Impacts on State Finances, Economy, and the Ratification of UNCAC - Wahyu Agatha, Safira; Puasa Handayani, Emi; Mardian Yoel, Siciliya (Estudiante Law Journal, 2024)
This study aims to analyze the differences in meaning between "causing financial losses to the state" and "causing economic losses to the state" as stipulated in Law Number 20 of 2001 on the Eradication of Corruption (Anti-Corruption Law) and the implications of the ratification of the United Nations Convention Against Corruption (UNCAC) 2003 on the provisions of the law. The research employs a normative juridical method with a legislative and conceptual approach. The findings indicate that the term "causing financial losses to the state" has a narrower scope compared to "causing economic losses to the state," which encompasses broader dimensions. UNCAC 2003 does not explicitly define either term but categorizes any form of harm to state assets as corruption. Additionally, UNCAC establishes five formats for international cooperation, including extradition and joint investigations, which can strengthen anti-corruption efforts. In conclusion, harmonizing the provisions of the Anti-Corruption Law with UNCAC is necessary to clarify definitions, enhance legal certainty, and promote economic stability. It is recommended to implement stricter measures regarding UNCAC's cooperation framework.